Peran Efikasi Diri (Self Efficacy) terhadap Kemampuan Pemecahan Masalah Matematika - Somawati Somawati (Jurnal Konseling dan Pendidikan, 2018)
Mathematical problem solving ability is surely the must-have any students in doinga math problem that is abstract. But many of the students who have not been able to use the problem-solving ability in doing a math problem. Many of them assumed that mathematics is a difficult lesson, and it usually requires a high concentration oflearning math. So the efficacy of self (self efficacy) is in need of students to cope with these problems. Self-efficacy (self efficacy) refers to the belief that relates to the ability and willingness of a student to achieve and complete tasks and results of the study with the target time has been determined and self efficacy refers to the consideration of how big someone's beliefs about their ability to perform a number of learning activities and their ability to complete tasks. Students who have a good self-efficacy will be successful in theirlearning activities andcanperform academic duties smoothly likewise viceversa if the efficacy in low students then have students will quickly give up on any problems in dealing with. Hence the need for self-efficacy so that arise from the student is either the later will provide confidence in the ability of students in solving mathematical problems.